2021
DOI: 10.1039/d0fo02382e
|View full text |Cite
|
Sign up to set email alerts
|

The main anthocyanin monomer of Lycium ruthenicum Murray induces apoptosis through the ROS/PTEN/PI3K/Akt/caspase 3 signaling pathway in prostate cancer DU-145 cells

Abstract: Pt3G inhibits DU-145 cell proliferation and induces apoptosis through the ROS/PTEN/PI3K/Akt/caspase-3 signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…The main compound was identified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS). The main anthocyanin compound from the fruits of L. ruthenicum was 3- O -[6- O -(4- O -(trans-p-coumaroyl)-a- l -rhamnopyranosyl)-b- d -glucopyranoside]-5- O -[b- d -glucopyranoside] ( Figure S1 ), which is consistent with previous results [ 13 , 14 ].…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…The main compound was identified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS). The main anthocyanin compound from the fruits of L. ruthenicum was 3- O -[6- O -(4- O -(trans-p-coumaroyl)-a- l -rhamnopyranosyl)-b- d -glucopyranoside]-5- O -[b- d -glucopyranoside] ( Figure S1 ), which is consistent with previous results [ 13 , 14 ].…”
Section: Methodssupporting
confidence: 91%
“…It has been reported that the fruits of L. ruthenicum are rich in anthocyanins. 3- O -[6- O -(4- O -(trans-p-coumaroyl)-a- l -rhamnopyranosyl)-b- d -glucopyranoside]-5- O - [b- d -glucopyranoside] ( Figure S1 ) is considered to be the main component of anthocyanin from the fruits of L. ruthenicum [ 13 , 14 ]. It has been reported that anthocyanins from the fruits of L. ruthenicum (ACN) possess a wide range of biological functions, including antioxidant and anti-inflammatory properties and can change the gut microbiota and reduce the risk of chronic diseases, such as obesity [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Akt inhibitor MK-2206 was reported to induce apoptosis in several different types of AML cells (MV-4-11, MOLM-13, OCI/AML3, and U-937). It is well accepted that some apoptotic death-related proteins are downstream of the PI3K/Akt pathway, such as caspase-3 and Bad (Nepstad et al 2020;Li et al 2021). Therefore, our data suggest that inhibition of PI3K/Akt may be involved in the induction of the anti-AML action of leonurine.…”
supporting
confidence: 52%
“…These researchers found that the anthocyanin monomer inhibits the proliferation of cell and induces apoptosis through the ROS/PTEN/PI3K/Akt/caspase 3 signaling pathway. 129 In a similar fashion, Pal et al revealed that delphinidin reduces cancer cell proliferation via inhibiting phosphorylation of Akt and MAPKs, and activation of PI2K. 130 On the other hand, Lim and Song demonstrated that delphinidin prevents the proliferation of ovarian cancer cells by deactivating ERK1/2 mitogen-activated protein kinase and PI3K/Akt signaling cascades.…”
Section: Discussion: Redox Regulation and Therapeutic Perspectives Of...mentioning
confidence: 96%